Pelatihan Kader Posyandu Sebagai Upaya Pencegahan Stunting Pada Balita Di Wilayah Kerja Kelurahan Jatimulya, Cilodong, Kota Depok, Jawa Barat - Lili Indrawati; Dinni Agustin (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2023)
Stunting is a condition in which toddlers have less length and height when compared to age caused by multidimensional factors, namely poor nutrition experienced by toddlers, lack of mother's knowledge about health and nutrition which has an impact on the level of intelligence, susceptibility to disease. One of the factors that plays an active role in early detection of stunting is the role of a mother under five and cadres. The stunting prevalence rate in Depok in 2021 is seen at 3.5 percent, namely 3,675 out of 105,127 toddlers in Depok City. This data has decreased from February 2021 by 4.7 percent as many as 4,923 out of a total of 102,815 toddlers in Depok. Even though there has been a decrease in numbers, in kel. Jatimulya Kec. Cilodong, Depok, there is a fairly high number of stunting cases, namely 47 cases in 9 RWs. For this reason, training was carried out for cadres and mothers with toddlers related to stunting in the working area of ​​Kel. Jatimulya with the aim of being able to prevent stunting. The results of the training are expected to be able to empower health cadres in carrying out their duties in providing counseling to the community, especially pregnant women and mothers with toddlers in a consistent and sustainable manner so as to improve cadre performance in stunting prevention and optimal posyandu services. Keywords: stunting, cadre, training